An LADM–based model to facilitate land tenure reform of rural homesteads in China. (September 2022) - Xu, Zhongguo; Zhuo, Yuefei; Li, Guan; Bennett, Rohan Mark; Liao, Rong; Wu, Cifang; Wu, Yuzhe
Abstract: The Land Administration Domain Model (LADM), an international standard (ISO 19152:2012), provides a conceptual data model for land administration. This study applies the LADM model to a previously unexplored case: the administration of homestead lands (residential lands) in rural China. In China, rural homestead tenures have been altered through several iterations since 1949, variously serving economic development, political governance and social security objectives. An intended contemporary reform of the homestead tenure system is based upon: (1) collective ownership by local communities; (2) qualification rights, a kind of personal servitude to safeguard the social security of individual community members; and (3) use rights, usufructuary interests offering management options to promote economic development. This work shows it is possible to translate this tripartite entitlement reform of rural homesteads into an LADM profile, with rights, persons, and land forming the base components. Four (sub) packages are formed, namely, Party, Administrative, Spatial Unit and Surveying and Representation. The work finds the LADM-based model, applied to the administration of China's rural homesteads, could facilitate the land tenure reform of rural homesteads, enable interoperability with other aspects of land administration, and could support national responses to those Sustainable Development Goals (SDGs) relating to poverty eradication, rural revitalization and intensive land use. Highlights: The evolution of rural homestead property system since the foundation of People's Republic of China is summarized. The existing rural homestead rights structure after the tripartite entitlement reform is discussed. An LADM-based rural homestead administration system for facilitating land tenure reform is developed.